PENGARUH KESIAPAN BELAJAR DAN KEMAMPUAN BERHITUNG TERHADAP HASIL BELAJAR MATEMATIKA - Diana Zuschaiya; Endras Wari; Yuni Agustina; Siti Lailiyah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research aims to know the level of learning readiness, numeracy skills, and mathematics learning outcomes of students, as well as to determine the effect of learning readiness and numeracy skills on mathematics learning outcomes. Sampling was done by purposive sampling so that the fifth grade students at MI Islamiyah Bumiayu were selected as samples in this research. The method used in this research is quantitative research methods with data collection techniques documentation, questionnaires, and tests. The research instrument test and questionnaire were analyzed using multiple regression analysis. The results showed that there was an influence between learning readiness and mathematics learning outcomes, and there was an influence between numeracy skills and mathematics learning outcomes with the magnitude of the effect of both of them by 88%.